Pengaruh Pemutihan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor dengan Pendapatan sebagai variabel Moderating - Muarif Leo; Winda Ayu Virginia; Irmawati Alimuddin; Herman Herman; Muhammad Resky Arwana (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to determine the effect of motor vehicle tax waiver policy on taxpayer compliance and how income moderates the effect of motor vehicle tax waiver policy on motor vehicle taxpayer compliance. The type of research used is quantitative research with primary data. The data technique collection is a questionnaire media. The population in this case is taxpayers who are served by the SAMSAT office region Baubau, South Est Sulawesi which utilizes the motor vehicle tax waiver policy, totaling 10,600 taxpayers. by using the Slovin formula, the minimum number of samples is 99. The sample determination uses purposive sampling method. Next, the researchers distributed questionnaires. The number of questionnaires that can be processed is 81 questionnaires while the rest cannot be processed because they are incomplete or not returned. The data analysis technique in this research is Moderated Regression Analysis (MRA). The results showed that the motor vehicle tax whitening policy had no significant effect on motor vehicle tax compliance. Taxpayer income has a significant and positive effect on taxpayer compliance with motor vehicle taxes. Taxpayer income has no significant effect on the relationship between motor vehicle tax waiver policy and motor vehicle tax compliance. This study also shows that the income variable is categorized as a moderating predictor variable.